Shattered dreams? an oral history of the South African AIDS epidemic - Oppenheimer, Gerald M.; Bayer, Ronald (New York ; Oxford : Oxford University Press, 2007)
Based on extended interviews with almost 90 doctors and nurses, 'Shattered Dreams?' is an oral history of how physicians and nurses in South Africa struggled to contend with the world's most catastrophic AIDS epidemic.
Description based on print version record.
Includes bibliographical references and index.
Keywords: AIDS (Disease) -- South Africa -- History; Oral history -- South Africa